Manual Conservation of Supplemental Oxygen in Low-Resource Settings During the COVID-19 Pandemic. Issue 2 (18th April 2022) - Lampotang, Samsun; DeStephens, Anthony; Zarour, Ilana; Lizdas, David; Gravenstein, Nikolaus; Johnson, William; Acar, Yahya; Feldman, Jeffrey M.
Summary Statement: Using a simulated adult COVID-19 patient with hypoxemia, we investigated whether caregivers interrupting oxygen flow by manually occluding oxygen tubing with pliers during exhalation can conserve oxygen while maintaining oxygenation. Oxygen pinching reduced oxygen use by 51% to 64%, maintained simulated oxygen saturation between 88% and 90%, and increased simulated average alveolar partial pressure of oxygen from a room air baseline of approximately 131 to 294–424 mm Hg compared with 607 mm Hg with 10 liters per minute (LPM) continuous oxygen flow. Simulation provided a methodology to rapidly evaluate a technique that has begun to be used with COVID-19 patients in low-resource environments experiencing an acute oxygen shortage.